α-Bisabolol alleviates doxorubicin-induced cognitive dysfunction in rats via enhancing the hippocampal BDNF/TrKB signaling and inhibiting neuroinflammation - Elazab, Sara T.; Hsu, Walter H. (Frontiers in Pharmacology, 2025)
Chemofog is a serious sequela commonly manifested among cancer patients receiving doxorubicin (DOX) chemotherapy. Our goal was to explore the abrogative action of α-Bisabolol (BISA), a phytochemical sesquiterpene, against DOX-induced cognitive deficit. Rats were allocated into 5 groups: Group I: control; Group II received BISA orally (100 mg/kg/day for 4 weeks); Group III received DOX (2 mg/kg/week/i.p.) for 4 weeks; Groups IV and V were administered BISA orally at 50 and 100 mg/kg, respectively plus DOX, i. p. Results: 1) BISA attenuated DOX-induced chemofog as shown in memory-related behavioral tests. 2) BISA restored the hippocampal histological structure and redox homeostasis via diminishing MDA content and upregulating Nrf2 and HO-1 genes. 3) BISA mitigated DOX-induced neuroinflammation through reducing NF-kB, TNF-α, IL-6, IL-1β, and GFAP expressions. 4) BISA repressed the hippocampal apoptosis via downregulating Bax gene and upregulating Bcl-2 gene. 5) BISA enhanced the synaptic plasticity by activating the BDNF/TrKB signaling and increasing the levels of neurotransmitters that enhance memory, i.e., ACh, 5-HT, and DA. BISA at 100 mg/kg/day exerted a better neuroprotection than BISA at 50 mg/kg/day. Thus, BISA may protect cancer patients from cognitive disorders caused by DOX.